2017
DOI: 10.1371/journal.pone.0169124
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Stemness Factor Sox2 in Gastric Cancer Is Associated with Tumor Location and Stage

Abstract: Cancer stem cells (CSCs) are thought to be the "root" of cancer. Although stemness-related factors ALDH1A1 and Sox2 have been used as markers to identify gastric CSCs, the expression pattern and significance of these factors in gastric cancer have not been sufficiently demonstrated. In this study, the expressions of ALDH1A1 and Sox2 were detected by immunohistochemistry in 122 gastric cancer specimens. And the correlation between Sox2 or ALDH1A1 expression and clinicopathological parameters and overall surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…According to research, SOX2, a major transcription factor is regarded as a stemness-related factor. It has been demonstrated that SOX2 is associated with various types of cancers and has been used as a marker to identify cancer stem cells (34). Furthermore, SOX2 suppression is mandatory for cellular differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…According to research, SOX2, a major transcription factor is regarded as a stemness-related factor. It has been demonstrated that SOX2 is associated with various types of cancers and has been used as a marker to identify cancer stem cells (34). Furthermore, SOX2 suppression is mandatory for cellular differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…This is parallel to the results of Basat et al [44] and Du et al [53], who reported a positive association between SOX2 expression with poor differentiation and advanced tumor stage. On the contrary, Lin et al [54] stated that SOX2 overexpression was associated neither with the overall survival nor with the other clinicopathological factors including grade and stage, while Yang et al [23] found that SOX2 positive expression was associated with shorter survival in patients at early-stage cancers, but not at an advanced stage. These conflicting results can be attributed to a lack of understanding the role of SOX2 as an oncogene or tumor suppressor in GC.…”
Section: A -Basic Sciences Pathologymentioning
confidence: 99%
“…Gastric CSCs can be enriched with several defined markers, including CD44, aldehyde dehydrogenase (ALDH), and Lgr5 [7,8]. Stemness markers such as SOX2 and Oct-3/4 have also been accepted for the identification of gastric CSCs [9]. However, the key components and molecular mechanisms contributing to self-renewal and tumorigenicity of gastric CSCs are largely unknown.…”
Section: Introductionmentioning
confidence: 99%